2020
DOI: 10.5811/westjem.2020.4.43387
|View full text |Cite
|
Sign up to set email alerts
|

Fall Prevention Knowledge, Attitudes, and Behaviors: A Survey of Emergency Providers

Abstract: Introduction: Falls are a frequent reason geriatric patients visit the emergency department (ED). To help providers, the Geriatric Emergency Department Guidelines were created to establish a standard of care for geriatric patients in the ED. We conducted a survey of emergency providers to assess 1) their knowledge of fall epidemiology and the geriatric ED guidelines; 2) their current ED practice for geriatric fall patients; and 3) their willingness to conduct fall-prevention interventions. Methods: We conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Given the time pressures ED clinicians face, ED clinicians are likely to benefit from additional professionals to assist with time-consuming fall screening or fall prevention interventions as nurses, physical therapists, pharmacists, and geriatricians. 14 Engaging these partners in the ED rather than relying on referral to an outpatient clinic alone is important, because several studies reviewed here showed that ED fall patients rarely attended outpatient fall clinics after referral. 49,85 The group also identified that EMS personnel could play an important role in assessing fall…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Given the time pressures ED clinicians face, ED clinicians are likely to benefit from additional professionals to assist with time-consuming fall screening or fall prevention interventions as nurses, physical therapists, pharmacists, and geriatricians. 14 Engaging these partners in the ED rather than relying on referral to an outpatient clinic alone is important, because several studies reviewed here showed that ED fall patients rarely attended outpatient fall clinics after referral. 49,85 The group also identified that EMS personnel could play an important role in assessing fall…”
Section: Discussionmentioning
confidence: 98%
“…8 Although falls are common and costly, 9 and recent evidence suggest that falls may be preventable in the ED setting, 4,7,10 ED-initiated fall screening and prevention efforts are not widespread, 11 perhaps due to the ED environment; limited resources in time and staffing are barriers to implementing impactful change in ED management of falls. [12][13][14] Given the mortality and morbidity associated with falls, there has been interest within emergency medicine to address falls and initiate ED-based fall prevention efforts. The Society for Academic Emergency Medicine (SAEM) Geriatric Emergency Medicine Task Force recognized fall prevention as one of three priority areas over 10 years ago.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…[29][30][31] The recent randomized controlled trial evaluating the GAPCare prevention program among ED patients, in contrast to STRIDE, showed a 50% reduction in return ED visits for falls. 32 Despite numerous guidelines recommending screening for mobility and fall risk in the ED, 5,19,26 and the existence of validated screening tools for mobility and falls risk, this screening has had limited uptake: studies suggest providers understand the importance of falls prevention, but have limited willingness to spend time on this task, 33 and often miss opportunities to modify falls risk. 34 Recent work has shown that using machine learning algorithms, return visits for falls can be predicted using only existing EHR data with discriminative capability similar to in-person screening that included functional testing.…”
Section: Use Case: Fallsmentioning
confidence: 99%
“…In a prior study, ED clinicians (physicians and advanced practice providers) have reported they are not willing to spend much time on fall risk identification and management, given tremendous time pressures and ED crowding, and a potential lack of understanding regarding the implications of a fall on older adults [ 15 ]. However, interventions during or soon after an ED visit might be a window of opportunity, given patients might be open to intervention at that time [ 16 ].…”
Section: Introductionmentioning
confidence: 99%